KEPASTIAN HUKUM KEKAYAAN INTELEKTUAL TERHADAP KARYA ILMIAH YANG DIHASILKAN CHATGPT - Chama Lamellosa Nararya; Sudirman; Wahyudi Umar (Jurnal Hukum Lex Generalis, 2024)
This research aims to examine the legal certainty of scientific works produced by ChatGPT. This study uses the type of normative research and the legislative approach to examine various legal rules as the focus of the research. by using primary and secondary legal materials. The results of the study show that ChatGPT cannot be said to be the creator of the Copyright Law in Indonesia and is not entitled to copyright for its work. The current regulation in Indonesia does not mention AI more clearly. However, the law follows human development in the future. So, the government must be clearer and more decisive in setting AI rules in Indonesia, which is growing.